INTEGRATING ENGINEERING AND SUSTAINABLE ACCOUNTING TO ACHIEVE ENVIRONMENTAL SUSTAINABILITY: AN APPLIED STUDY OF IRAQI OIL COMPANIES (World Economics and Finance Bulletin, 2024)
This research seeks to establish how engineering activities can be incorporated with sustainable accounting into Iraqi oil firms to improve the environmental and accounting aspects. Analyzing both quantitative and qualitative data, the study quantitatively investigates the effectiveness of this integration while qualitatively examining the perceptions of this integration through a case study. There is a mixed relationship between the integration of the engineering data and the perceived benefits based on the quantitative data and qualitative responses regarding its contribution to sustainability initiatives and decisionmaking, for which there is a positive perception, albeit due to a limited quantitative statistical influence of the demographic variables. The study lays down enormous future consequences for the oil sector. It indicates that properly integrating engineering and accounting disciplines can revolutionize environmental policies and enhance financial reporting techniques. These insights call for optimizing the current business practices to maximize the benefits of integrating engineering and accounting for the conservation of the environment and enhancing economic performance